In vitro characterisation of Span™ 65 niosomal formulations containing proteins - Rochdy Haj-Ahmad, Rita; Ali Elkordy, Amal; Shu Chaw, Cheng (Current Drug Delivery, 2015)
Proteins can be encapsulated in niosomes as they are known to protect proteins against the surrounding env ironment. Niosomes of Span™ 65/cholesterol/pluronic® F -127 were prepared by thin film hydration method. Insulin and lysozyme were chosen as model proteins. Niosomes were chara c-terised for morphology by Transmission Electron M icroscopy (TEM) and vesicles size using Dynamic Light Scattering. The entrapment efficiency of protein in niosomes was determined by complete vesi-cle disruption using 50:50% isopropanol:buf fer, followed by analysis of the resulting so lutions by HPLC method. Thermal behaviour of the niosomes was investigated using Differential Scanning Calo-rimetry (DSC). Protection of proteins against simulated gastric fluid (SGF) and simu lated intestinal fluid (SIF) were also assessed. The results showed that niosomes prepared with diffe r ent molar ratios % of Span™ 65, cholesterol and pluronic®F -127 successfully produced with insulin and lysozyme. For insulin co n taining niosomes, the ratio % of 64.7 (Span™ 65): 32.3 (cholesterol): 3.0 (pluronic® F - 127) produced the highest protein encapsulation eff i-ciency and the smallest vesicle size of 653.6 nm. For lysozyme containing niosomes, the maximum pr o tein encapsulation was found in 72.75/24.25/3.00% molar ratio of Span™ 65/cholesterol/pluronic® F -127 niosomes with vesi cle size of 627.3 nm. The release study of proteins from the niosomal preparations in simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) revealed that insulin and lysozyme efflux from the niosomes is a biphasic process. The results indicate that Span™ 65 niosomes could be developed as controlled release dosage forms for delivery of peptides and proteins such as insulin and lysozyme.
Keywords: lysozyme